Biomarkers in Pancreatic Adenocarcinoma - Joza, Nicholas; Saif, Muhammad Wasif (JOP. Journal of the Pancreas, 2014)
Pancreatic adenocarcinoma is a highly aggressive cancer, with a median patient survival of less than one year. Clinically useful biomarkers capable of accurately assessing prognosis, as well as response to therapy, are urgently needed. At the 2014 ASCO Annual Meeting, Maus et al. (Abstract #e15199) and Neuzillet et al. (Abstract #e15200) present data on use of c-met as a prognostic biomarker, and Shultz et al. (Abstract #4133) use a multiplex antibody panel to identify predictive markers of response to gemcitabine and erlotinib. Image: Green space by the Jaharis Center and Tufts Medical Center. Boston, MA, USA